2019
DOI: 10.48550/arxiv.1903.01002
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A note on the Turán number of a Berge odd cycle

Abstract: In this note we obtain upper bounds on the number of hyperedges in 3-uniform hypergraphs not containing a Berge cycle of given odd length. We improve the bound given by Füredi and Özkahya. The result follows from a more general theorem. We also obtain some new results for Berge cliques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Füredi and Özkahya [21] obtained better constant factors (depending on k). Further improvements were obtained for even k by Gerbner, Methuku and Vizer [24], also by Gerbner, Methuku and Palmer [23], and for odd k by Gerbner [22]. For s ≥ 4, Győri and Lemons [26] showed that ex(n, s,…”
Section: Preliminariesmentioning
confidence: 96%
“…Füredi and Özkahya [21] obtained better constant factors (depending on k). Further improvements were obtained for even k by Gerbner, Methuku and Vizer [24], also by Gerbner, Methuku and Palmer [23], and for odd k by Gerbner [22]. For s ≥ 4, Győri and Lemons [26] showed that ex(n, s,…”
Section: Preliminariesmentioning
confidence: 96%
“…Our proof is based on the proof of Lemma 6. We use the following lemma from [11] (most of which already appears in [13]).…”
Section: Generalized Hypergraph Turán Problemsmentioning
confidence: 99%